Canonical Stimulation of the NLRP3 Inflammasome by Fungal Antigens Links Innate and Adaptive B-Lymphocyte Responses by Modulating IL-1β and IgM Production - Ali, Mohamed F.; Dasari, Harika; Van Keulen, Virginia P.; Carmona, Eva M. (Frontiers in Immunology, 2017)
The NLRP3 inflammasome is activated in response to different bacterial, viral and fungal pathogens and serves as modulator of different pattern recognition receptors signaling pathways. One of the main functions of NLRP3 is to participate in IL-1beta maturation which is important in the host defense against Pneumocystis and other fungal infections. However, dysregulation of NLRP3 and IL-1beta secretion are also implicated in the pathophysiology of many auto-inflammatory disorders. Often time’s inflammatory flares are preceded by infectious illnesses questioning the role of infection in autoimmune exacerbations. However, we still do not fully understand the exact role that infection or even colonization plays as triggers of inflammation. Herein, we investigated the role of NLRP3 in circulating B-lymphocytes following activation with two major microbial antigens (beta-glucan and CpG) NLRP3 was determined essential in two independent B-lymphocytes processes: pro-inflammatory cytokine secretion and antibody regulation. Our results show that the β-glucan fungal cell wall carbohydrate, stimulated B-lymphocytes to secreted IL-1β in a process partially mediated by Dectin-1 activation via SYK and the transcription factors NF-kappaB and AP-1. This IL-1beta secretion was regulated by the NLRP3 inflammasome and was dependent on potassium efflux and Caspase-1. Interestingly, B-lymphocytes activated by unmethylated CpG motifs, found in bacterial and fungal DNA, failed to induce IL-1beta. However, B-lymphocyte stimulation by CpG resulted in NLRP3 and Caspase-1 activation and the production and secretion of IgM antibodies. Furthermore, CpG-stimulated IgM secretion, unlike beta-glucan-mediated IL-1beta production, was mediated by the mammalian target of rapamycin (mTOR). Inhibition of NLRP3 and the mTOR pathway in CpG activated B-lymphocytes resulted in impaired IgM secretion suggesting their participation in antibody regulation. In conclusion, this study describes a differential response of NLRP3 to beta-glucan and CpG antigens and identifies the NLRP3 inflammasome of human circulating B-lymphocytes as a modulator of the innate and adaptive immune systems.